2015
DOI: 10.1242/bio.20149589
|View full text |Cite
|
Sign up to set email alerts
|

Shroom3 functions downstream of planar cell polarity to regulate myosin II distribution and cellular organization during neural tube closure

Abstract: Neural tube closure is a critical developmental event that relies on actomyosin contractility to facilitate specific processes such as apical constriction, tissue bending, and directional cell rearrangements. These complicated processes require the coordinated activities of Rho-Kinase (Rock), to regulate cytoskeletal dynamics and actomyosin contractility, and the Planar Cell Polarity (PCP) pathway, to direct the polarized cellular behaviors that drive convergent extension (CE) movements. Here we investigate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
121
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(140 citation statements)
references
References 80 publications
18
121
0
1
Order By: Relevance
“…Dvl2 also exhibits a planar polarized distribution along mediolaterally oriented membranes (Fig. 2), being strongly recruited there by Celsr1 (McGreevy et al, 2015;Nishimura et al, 2012). Dvl2 asymmetry to posterior versus anterior membranes, if present in the neural plate, was not detectable in these studies.…”
Section: Neuroepithelial Ce Movementsmentioning
confidence: 60%
See 1 more Smart Citation
“…Dvl2 also exhibits a planar polarized distribution along mediolaterally oriented membranes (Fig. 2), being strongly recruited there by Celsr1 (McGreevy et al, 2015;Nishimura et al, 2012). Dvl2 asymmetry to posterior versus anterior membranes, if present in the neural plate, was not detectable in these studies.…”
Section: Neuroepithelial Ce Movementsmentioning
confidence: 60%
“…Shroom3 is an apically enriched actin-binding protein that recruits Rho-associated kinase (Rock) to activate myosin II, driving apical constriction and neural tube closure (Nishimura and Takeichi, 2008). A recent report demonstrated that, in the mouse neural plate, Shroom3 and Rock become polarized to mediolaterally aligned membranes by Dvl2 (McGreevy et al, 2015). Daam1, which is a formin homology protein that directs nucleation and elongation of actin filaments, also functions as an adaptor linking Dvl to RhoA in multiple PCP processes (Habas et al, 2001).…”
Section: Neuroepithelial Ce Movementsmentioning
confidence: 99%
“…SHROOM3 mediates the PCP pathway (McGreevy et al 2015) and plays an essential role in regulating cytoskeletal dynamics (Zalewski et al 2016), which are critically important during the closure of the neural tube. Recently, de novo LoF mutations in SHROOM3 were experimentally associated with the development of NTDs, suggesting that these variants may also contribute to the genetic etiology of severe human NTDs (Lemay et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous animal models have demonstrated that homozygous Shroom3 mutant embryos exhibited exencephaly (Hildebrand and Soriano 1999). Shroom3 interacts genetically with the PCP components Vangl2 and Wnt5a, and depletion of Shroom3 and Vangl2 or Wnt5a can drastically increase the penetrance and severity of NTDs (McGreevy et al 2015). The PCP pathway is highly dosage sensitive, and over-or under-expression of PCP core genes in zebrafish and Xenopus embryos results in convergent extension defects (Roszko et al 2009; Wallingford 2005, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation